Do Ramadan Fasting Restrictions Alter Eating Behaviours in Obese Women? - Savas, Esen (Journal of religion and health, 2014)
Ramadan fasting can be considered as a kind of dietary restriction. Eating restriction is a risk factor for later development of eating disorders. The purpose of this study is to evaluate whether Ramadan fasting changes the eating behaviours of obese women. Our sample consisted of 34 obese women who fasted during the Ramadan month. The data were collected by using Questionnaire Form, Eating Attitude Test (EAT) and Bulimic Investigatory Test, Edinburgh (BITE). No statistically significant differences were found between the scores of EAT, BITE, BMI, which were administered within the weeks before and after Ramadan. According to our results, Ramadan fasting restrictions do not seem to change the eating behaviours of obese women.